2016
DOI: 10.2903/j.efsa.2016.4349
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of vitamin B2 (riboflavin and riboflavin 5’‐phosphate ester monosodium salt) produced by Bacillus subtilis for all animal species based on a dossier submitted by DSM

Abstract: 2Riboflavin is produced by two genetically modified Bacillus subtilis strains. Neither the production strains nor their recombinant DNA were detected in the final riboflavin products. Riboflavin 5'phosphate sodium is prepared by phosphorylation of riboflavin. The additives are safe for target animals with a wide margin of safety provided that the current use levels for riboflavin are not exceeded. Toxicological studies with the additive under assessment show that it has a low toxicity and do not indicate a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The nutrient requirements/recommendations of the target species for vitamin B 2 , the background levels of vitamin B 2 in feed materials and the tolerance to overdoses of vitamin B 2 were reviewed by the FEEDAP Panel in previous opinions (EFSA FEEDAP Panel, 2014, 2016, 2018b. The Panel concluded that the use levels based on the requirement/background levels would pose no safety concerns to the target species.…”
Section: Safety For the Target Species Consumer And Environmentmentioning
confidence: 99%
“…The nutrient requirements/recommendations of the target species for vitamin B 2 , the background levels of vitamin B 2 in feed materials and the tolerance to overdoses of vitamin B 2 were reviewed by the FEEDAP Panel in previous opinions (EFSA FEEDAP Panel, 2014, 2016, 2018b. The Panel concluded that the use levels based on the requirement/background levels would pose no safety concerns to the target species.…”
Section: Safety For the Target Species Consumer And Environmentmentioning
confidence: 99%
“…The FEEDAP Panel has adopted five opinions on the use of vitamin B 2 as a feed additive. Two opinions related to the safety and efficacy of vitamin B 2 (80%) as riboflavin produced with Bacillus subtilis KCCM-10445 for all animal species (EFSA FEEDAP Panel, 2014, 2018a, an opinion on the safety and efficacy of vitamin B 2 as riboflavin and riboflavin-5 0 -phosphate ester monosodium salt, produced by either Bacillus subtilis DSM 17339 or Bacillus subtilis DSM 23984 (EFSA FEEDAP Panel, 2016), and another opinion on the safety and efficacy of vitamin B 2 (riboflavin) produced by Ashbya gossypii (EFSA FEEDAP Panel, 2018b). The last one was related to the safety and efficacy of vitamin B 2 (riboflavin 5 0 -phosphate ester monosodium salt) for all animal species when used in water for drinking (EFSA FEEDAP Panel, 2018c).…”
Section: Additional Informationmentioning
confidence: 99%
“…In previous assessments, the FEEDAP Panel concluded that the supplementation of feed with riboflavin could not be of concern for the consumers (EFSA FEEDAP Panel, 2014, 2016, 2018b. However, apart from riboflavin, the toxicological profile of the other components of the additive, which is a fermentation product, has not been established, and therefore, uncertainties remain as regards to the safety for the consumers of food products obtained from animals receiving the additive under assessment.…”
Section: Safety For the Consumermentioning
confidence: 99%
“…Riboflavin absorption, its metabolic fate and its potential accumulation in edible tissues and eggs have been described in detail in previous opinions (EFSA FEEDAP Panel, 2014, 2016.…”
Section: Metabolic and Residue Studiesmentioning
confidence: 99%